SHAKESPEAREAN INTERTEXTUALITY IN AL AMMAR’S NOVELS: SILENCE IS A SENSE AND THE PACT WE MADE - Zeina Izzat Sadiq Zeidan (جامعة النجاح الوطنية, 2025)
This study focuses on the intertextuality apparent in Laila Al-Ammar's Novels, The Pact We Made and Silence is a Sense, specifically analyzing how both novels employ Shakespeare's The Tempest. It delves into Laila Al-Ammar's use of literary intertextuality to dismantle and question preexisting literary and social standards through investigating the character of Ariel, Desdemona, Prospero, and Caliban. Several subjects are considered via the perspective of intertextuality theory put out by Julia Kristeva, such as: Intertextuality to Reveal an Image of Colonization, Intertextuality Shows Mental Breakdown: Rape Trauma Syndrome, Intertextuality Presents Recognition of Self, and Intertextuality Emphasizes The Gaze of Others and Reputation. Therefore, to better understand the similarities and differences between the characters in Al-Ammar's work and those in Shakespeare's, this study takes a qualitative descriptive-analytical approach. By delving into the challenges faced by Dahlia and the unnamed narrator in Al-Ammar's novels, as well as those in The Tempest, the results show how intertextuality enhances novels by critiquing colonialism and social oppression and the psychological effects that stem from them. The resulting discussion sheds light on the interaction between the past and the present, investigating the agency of women, and tackles cultural and psychological trauma. Accordingly, there is a unique understanding of how classical and modern narratives interact by filling a gap in our understanding of Shakespeare's intertextuality in Arabic literature of the contemporary era.
التناص واقتباس شكسبير في روايات ليلى العمار: (الصمت إحساس) و (الوعد الذي قطعناه)